VD_FINDINFO HC / 2011 / 642 vom 17. Oktober 2011 - VD Tribunal cantonal (2011)
ÉMOLUMENT DE JUSTICE, DÉCISION SUR FRAIS, FRAIS JUDICIAIRES | 107 al. 2 CPC (CH), 241 al. 1 CPC (CH), 241 al. 3 CPC (CH), 22 al. 1 TFJC (2010)